Comparison of performance of digital hemoglobinometer over automated hematology analyzer for hemoglobin estimation and its user-friendliness among the pregnant women in selected district hospitals of Madhya Pradesh - Manju Toppo; Dinesh Kumar Pal; Devendra Gour; Veena Melwani; Manju Dubey; Archana Mishra (Wolters Kluwer Medknow Publications, 2019)
Context: There is a need for a simple screening method for the detection of anemia that can be used by public health workers in the field. Aims: The aim of this study was to compare two methods for hemoglobin estimation, i.e., automated hematology analyzer and Digital Hemoglobinometer, and to find out the sensitivity and specificity of Digital Hemoglobinometer for the estimation of hemoglobin. Subjects and Methods: A hospital-based cross-sectional study was carried out for 6 months from April to September 2017 in a District Hospital of five High Priority Districts of Madhya Pradesh. Two hundred and sixty antenatal females per district were selected for the study. Results: The mean hemoglobin by autoanalyzer is 10.19, and that by Digital Hemoglobinometer device is 9.89. Overall, sensitivity of Digital Hemoglobinometer for hemoglobin estimation was calculated to be 89.4% and specificity was calculated to be 63.6%. Positive predictive value was found to be 82.6% and negative predictive value was 75.8% compared against AutoAnalyser (gold standard). Conclusions: As the Digital Hemoglobinometer device has high sensitivity and specificity and good diagnostic accuracy, it must be used at the community level in resource-poor setting for hemoglobin estimation. In primary health-care conditions, Digital Hemoglobinometer can significantly reduce misdiagnosis of anemia compared with clinical assessment alone.